발달증진프로그램이 발달지연 아동 어머니의 양육 스트레스에 미치는 영향 - 유홍섭(Hong-Sup Yu); 이순정(Soon-Jeong Lee); 송동호(Dong-Ho Song) (Soa--chʻŏngsonyŏn chŏngsin ŭihak = Journal of child & adolescent psychiatry, 2009)
Objectives : We investigated the parenting stress and depressive mood of mothers with developmentally-delayed children and the effects of participation in a mother-child development promotion program on same. Methods : Subjects were the mothers of 20 developmentally-delayed children. The severity of the mothers' parenting stress was evaluated via the Korean version of the Parenting Stress Index, Short Form (K-PSI-SF) and the severity of their depressive symptoms were evalueted by the Korean version of the Beck Depression Inventory (K-BDI). Results : The mean K-PSI-SF score and mean K-BDI score for these mothers were 93.35 (SD=10.47) and 23.25 (SD=10.42), respectively. These scores correspond to high parenting stress and moderate depression. The mothers who participated in a mother-child attachment- promotion program showed significant decreases in their K-PSI-SF and KBDI scores. Conclusion : Our data suggest that a mother-child attachment promotion program with emphasis on child development is effective in reducing parenting stress and depressive mood in mothers of developmentally-delayed children.